1998
DOI: 10.1023/a:1008811814446
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An analytical approach is presented for determining the response of a neuron or of the activity in a network of connected neurons, represented by systems of nonlinear ordinary stochastic differential equations--the Fitzhugh-Nagumo system with Gaussian white noise current. For a single neuron, five equations hold for the first- and second-order central moments of the voltage and recovery variables. From this system we obtain, under certain assumptions, five differential equations for the means, variances, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…Numerical simulations have shown that for weak noises, the distribution of v(t) of the membrane potential of a single HH neuron nearly obeys the Gaussian distribution, although for strong noises, the distribution of v(t) deviates from the Gaussian, taking a bimodal form [22] [37]. Similar behavior of the membrane-potential distribution has been reported also in a FN neuron model [18] [38]. By using Eq.…”
Section: A Equation Of Motionssupporting
confidence: 66%
See 1 more Smart Citation
“…Numerical simulations have shown that for weak noises, the distribution of v(t) of the membrane potential of a single HH neuron nearly obeys the Gaussian distribution, although for strong noises, the distribution of v(t) deviates from the Gaussian, taking a bimodal form [22] [37]. Similar behavior of the membrane-potential distribution has been reported also in a FN neuron model [18] [38]. By using Eq.…”
Section: A Equation Of Motionssupporting
confidence: 66%
“…Similar population density approaches have been recently developed for a large-scale neuronal clusters [15,16]. The moment method initiated by Rodriguez and Tuckwell (RT) has been applied to single FN [17,18] and HH neurons [19,20]. When the moment method is applied to a single neuron model with K variables, K-dimensional stochastic DEs are replaced by (1/2)K(K + 3)-dimensional deterministic DEs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, such a property has been demonstrated in the case of FN oscillators, with representing a white noise process [22].…”
Section: Resultsmentioning
confidence: 93%
“…At the other end of the spectrum, the effect of noise on nonlinear contracting systems is bounded by where is the noise intensity – which can be arbitrarily large – and is the contraction rate of the system [21]. Between these two extremes, it has been shown analytically that some limit-cycle oscillators commonly used as simplified neuron models, such as FitzHugh-Nagumo (FN) oscillators, are basically unperturbed when they are subject to a small amount of white noise [22]. Yet, a larger amount of noise breaks this “resistance”, both in the state space and in the frequency space [Figures 1(A)–(D)].…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the noise intensity β is weak and that the distribution of state variables takes the Gaussian form concentrated near the means of (µ 1 , µ 2 ), as previously adopted [21] [22]. Numerical simulations for a single FN neuron have shown that for weak noises, the distribution of x(t) of the membrane potential nearly obeys the Gaussian distribution, although for strong noises, the distribution of x(t) deviates from the Gaussian, taking a bimodal form [26] [27]. Similar behavior of the membrane-potential distribution has been reported also in the HH neuron model [28] [29].…”
Section: A Basic Formulationmentioning
confidence: 92%